ANALISIS STRUKTURAL DAN NILAI MORAL PADA CERITA RAKYAT PUTERI DEWA GUNUNG LUMUT SERTA RELEVANSI DENGAN PEMBELAJARAN BAHASA INDONESIA DI SMP NEGERI 1 PENANGGALAN - Kamaruzzaman; Siburian, Panigoran; Purba, Christin Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this literary research is to explain the structure and moral value of the folk tale "Puteri Dewa Gunung Lumut" and its relevance to Indonesian language learning at SMP Negeri 1 Penanggalan. The approach used in this research is a qualitative approach. The research location is not bound by data collection. The search for data regarding the relevance of analysis to Indonesian language learning was carried out at SMP Negeri 1 Penanggalan. This research was carried out for 3 months from August to October 2024. Data collection in this qualitative research used several techniques. a) Observation or observation. b) Interview technique. c) Recording techniques (audio and audiovisual). d) Recording techniques. e) Documentation Techniques. f) Transcription techniques. Data analysis techniques use techniques descriptive analysis. The research results show that based on an analysis of the structure of the folk tale "Puteri Dewa Gunung Lumut" it is known that each element in the story builds the story into one folk tale. The most prominent moral value in this story is human relationships with other humans. This shows an attitude of willingness to sacrifice, love with kindness, and the obligation to protect women and children in life. The results of the analysis of this oral literature and its oral literature are also relevant to ATP Indonesian class IX with the learning objective "Students can discover local wisdom and report it in the right format. The relevance found is related to the context of teaching moral values, developing language skills, and cultural understanding to students.